Diversity in the early tertiary anthropoidean radiation in Africa. - Simons, E L (1992)
Between 1987 and 1991 recent field seasons in the Fayum Depression of Egypt have yielded five species and genera of primates that were earlier unknown. Three of these species and genera are described below. All these genera and species are known only from Fayum site L-41, which has been dated as of late Eocene age. In the Fayum, these 5 species from L-41 are added to 3 kinds of prosimians (1 species formally described) and 11 earlier named species of Anthropoidea. When certain undescribed species are added, the total of known Fayum primate species comes to 21, belonging to at least 10 genera, genera that, in turn, could belong to as many as seven families. This arguably represents more taxonomic diversity of primates, especially higher primates, than has been demonstrated before in one so spatially and temporally limited area. These facts argue that an important, perhaps primary, radiation of anthropoideans took place in the African Eocene.